Relationship between growth mindset and competitive motivation: a moderated parallel mediation model and feature importance analysis - Deng, Junchen; Wang, Zhipeng; Chen, Haiwei; Song, Bo (Frontiers in Psychology, 2025)
While growth mindset theory has been extensively studied in education, its influence on competitive motivation in sports contexts remains less understood. This study investigates how growth mindset (GM) affects competitive motivation (CM) among university athletes through stress response (SR) and basic psychological need satisfaction (BNS), with elite athlete status as a moderator. Analysis of data from 490 university athletes (250 elite, 240 non-elite) in Guangzhou revealed that GM positively relates to CM, partially mediated by reduced SR and increased BNS. Remarkably, elite athlete status demonstrated substantially stronger effects on these mediating pathways than GM itself, with elite athletes showing enhanced benefits from GM compared to non-elite peers. Feature importance analysis further identified dimension-specific predictors across different motivational aspects: autonomy most strongly predicted social recognition motivation, GM primarily influenced athletic ability improvement, while environmental factors and competition losses differentially affected entertainment and effort orientations. These findings expand GM applications in competitive sports and suggest that psychological interventions might yield stronger effects for elite athletes, highlighting the critical interplay between athletic development level and psychological factors in CM.